2012
DOI: 10.3389/fncom.2012.00066
|View full text |Cite
|
Sign up to set email alerts
|

Fusimotor control of spindle sensitivity regulates central and peripheral coding of joint angles

Abstract: Proprioceptive afferents from muscle spindles encode information about peripheral joint movements for the central nervous system (CNS). The sensitivity of muscle spindle is nonlinearly dependent on the activation of gamma (γ) motoneurons in the spinal cord that receives inputs from the motor cortex. How fusimotor control of spindle sensitivity affects proprioceptive coding of joint position is not clear. Furthermore, what information is carried in the fusimotor signal from the motor cortex to the muscle spindl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…The centrally encoded joint angle information is conveyed to the periphery by a plausible function of γ fusimotor control through regulating spindle sensitivity, so that the Ia signaling from spindle afferents is kept faithfully proportional to the joint angle during the movement and muscle contraction [54]. In our study, significant difference on the mean WP-LPSE values in each time interval exists among different angles of elbow flexion (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 71%
“…The centrally encoded joint angle information is conveyed to the periphery by a plausible function of γ fusimotor control through regulating spindle sensitivity, so that the Ia signaling from spindle afferents is kept faithfully proportional to the joint angle during the movement and muscle contraction [54]. In our study, significant difference on the mean WP-LPSE values in each time interval exists among different angles of elbow flexion (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 71%
“…We neglect other types of proprioceptive feedback, for example from Golgi tendon organs, which may provide a link to joint-based control (Kistemaker et al, 2013). Furthermore, more detailed representations of the proprioceptors (Loeb and Mileusnic, 2015) allow for a detailed analysis of, e.g., the role of alpha-gamma co-activation (Lan and Zhu, 2007;Lan and He, 2012).…”
Section: Model Assumptions and Limitationsmentioning
confidence: 99%
“…The physiological system of human motor control is not only highly redundant (Bernstein, 1967 ; Martin et al, 2009 ), but also endowed with intricate dual α and γ sensorimotor control (Granit, 1975 ; Pierrot-Deseilligny and Burke, 2005 ; Lan and He, 2012 ; Prochazka and Ellaway, 2012 ). Our understanding about how movements are organized and how muscles are coordinated in performing different tasks remains incomplete due to lack of in vivo data during behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The co-activation of γ motoneurons with α motor activity was generally viewed to compensate for the unloading effects of muscle contraction to spindle sensitivity. Using a realistic virtual arm (VA) model (He et al, 2013 ), Lan and He ( 2012 ) suggested a plausible function of γ s fusimotor control to convey centrally encoded joint angle information to the periphery through regulating spindle sensitivity, so that the Ia signaling from spindle afferents is kept faithfully proportional to the joint angle during movement and muscle contraction. This not only explains γ co-activation with α activity, but also supports the hypothesis that the γ s command reinforces the centrally planned kinematics of movement and posture by way of spinal circuits.…”
Section: Introductionmentioning
confidence: 99%